Leadership Training Program at Faculty of Psychology, Bosowa University - Purwasetiawatik, Titin Florentina; Ibrahim, Misykat Malik; Rasyid, Muhammad Nur Akbar (Newinera Publisher, 2024)
This study aims to describe the implementation of the Kirkpatrick model evaluation of levels 1, 2 and 3 of the student leadership training programs at the Faculty of Psychology, Bosowa University, Makassar. This study uses a mix method (quantitative-qualitative). This study involved 33 participants. Data were collected through questionnaires, interviews, observations, and documentation. The results of the study showed that level 1, participant reactions measured by a Kirkpatrick reaction sheet questionnaire, that leadership training participants were satisfied with the available schedule components and were very satisfied with the committee components, facilities, content, speakers and materials. At level 2, which was measured through a pre-post t-test, there was a change in participant knowledge and skills with a significant average learning evaluation value. At level 3, which was described from the interview results, there was a change in behavior in 4 components, namely personality, interpersonal communication, cooperation skills and leadership skills, although the changes were not significantly consistent for 33 participants within 1.5 months. The Kirkpatrick evaluation model is effective in assessing the level of participant satisfaction, increased knowledge and changes in behavior of leadership training participants. The leadership training program is very effective to be carried out continuously every year as an effort to shape the character of students who are ethical, innovative, broad-minded, and have global competitiveness. The material provided is more varied, adjusted to the development and context of the generation. Carrying out activities according to the training guidelines and inviting more students to actively participate.